Planar ultra wide band antenna with band rejector - Nada, Ahmed Hafedh (2020)
Ultra wideband (UWB) that occupies the range of (3.1-10.6) GHz was proposed due to the progressive need of high data rates for modern applications and lack of bandwidth in lower frequencies. UWB systems have become fundamental in high speed wireless communications that are used for short range indoor applications due to their features such as low power consumption, small size, and low cost. Antennas are essential part of the UWB systems, especially planar antennas because they can be fabricated easily. But an electromagnetic interference may occur due to the existence of narrowband systems like wireless local area networks (WLANs) that operate at 5.8 GHz which is inside the UWB band. Therefore, UWB antennas should also avoid those frequencies in order to obtain more efficient operating system. Thus, special structure known as electromagnetic band gap (EBG) structures can be used as band rejecter in order to reject the interlaced band. This project focuses on EBG structures and how they can be incorporated with UWB antennas. Firstly, a new planar UWB antenna structure that operates at UWB frequency range (3.08-10.7 GHz) is presented using half ground plane method. The antenna achieved a peak gain of 5.26 dB. Moreover, it exhibits a radiation efficiency of higher than 74% over its bandwidth. Then, a study is conducted on EBG mushroom-like shape using suspended transmission line method. Next, a new EBG structure that operates at 5.8 GHz is proposed. Shortly after, the designed structures are incorporated together to perform the intended function of an UWB with a gap at 5.8 GHz. The new structure has a notch of 0.7 GHz in terms of (S11=-10 dB), whereas the rejected band is 0.18 GHz. Additionally, outside the rejected band, the performance of the UWB antenna was not much affected by adding the EBG. In fact, excluding the notch, the antenna bandwidth increased to cover the range from 2.91 GHz to 11 GHz. FR4 substrate with is used for all designs. Simulations are conducted using CST software, and all the results are presented into graphs and tables.